2017
DOI: 10.1371/journal.pone.0169904
|View full text |Cite
|
Sign up to set email alerts
|

Association between Social Relationship and Glycemic Control among Older Japanese: JAGES Cross-Sectional Study

Abstract: AimThe present study examined whether social support, informal socializing and social participation are associated with glycemic control in older people.MethodsData for this population-based cross-sectional study was obtained from the Japan Gerontological Evaluation Study (JAGES) 2010 linked to the annual health check-up data in Japan. We analyzed 9,554 individuals aged ≥65 years without the certification of needed long-term care. Multivariate logistic regression models were used to assess the effect of social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…In general, greater amounts of social relationships contributed to higher SRH, especially good relationships with friends. This is consistent with previous studies that demonstrated better social relationships had protective effects against early death and physical disability 14 ) , and occasionally meeting with friends was associated with better glycemic control in older Japanese subjects 15 ) . Social support, not only from family members but also from neighbors and friends, was reported to be related to a low prevalence rate of depression in older Japanese people 16 ) .…”
Section: Discussionsupporting
confidence: 93%
“…In general, greater amounts of social relationships contributed to higher SRH, especially good relationships with friends. This is consistent with previous studies that demonstrated better social relationships had protective effects against early death and physical disability 14 ) , and occasionally meeting with friends was associated with better glycemic control in older Japanese subjects 15 ) . Social support, not only from family members but also from neighbors and friends, was reported to be related to a low prevalence rate of depression in older Japanese people 16 ) .…”
Section: Discussionsupporting
confidence: 93%
“…The pathways underlying the association between social networks and ACP discussions among Japanese older adults have not, to the best of our knowledge, been clarified. Social engagement might be one functional pathway that mediates between social networks and ACP discussions; evidence of this is found in several recent studies regarding the effect of social engagement on other health-promoting behaviors among Japanese older adults, such as dental hygiene or better glycemic control [ 35 , 36 ]. Social support is another, according to the aforementioned studies conducted in the U.S. [ 13 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Possible answers were ≥4 d·wk −1 , 2–3 d·wk −1 , 1 d·wk −1 , 1–3 d·month −1 , a few times a year, or zero. We defined participating 1 d·month −1 or more often as “participation” in a sports group ( 18 , 25 ) and aggregated individual-level sports group participation by community area as a community-level independent variable. Previous research ( 18 ) indicates that the correlation of the proportion of older individuals with depressive symptoms (GDS ≥ 5) in areas with community-level sports group participation 1 d·month −1 or more often ( r = −0.355) tended to be strong compared with that with community-level sports group participation 1 d·wk −1 or more often ( r = −0.314).…”
Section: Methodsmentioning
confidence: 99%